Do Superordinate Identification and Temporal/Social Comparisons Independently Predict Citizens’ System Trust? Evidence From a 40-Nation Survey - Caricati, Luca; Owuamalam, Chuma Kevin; Bonetti, Chiara (Frontiers in Psychology, 2021)
Do superordinate ingroup bias, temporal and social comparisons offer unique standalone explanations for system justification? We addressed this question using the latest World Value Survey (7th Wave), combining the responses of 55,721 participants from 40 different nations worldwide. Results from a random slope multi-level model showed that superordinate (national) identification, temporal comparison (i.e., one’s outcomes relative to those of one’s parents at different time points) and social comparison (based on income levels) were independent and positive predictors of system justification. Specifically, system justification increased when national identification was high, when income increased (i.e., socio-economic comparison was positive) and when citizen’s outcomes improved relative to their parents’ outcomes at relevant time points (i.e., temporal comparison was positive). Incidentally, we also observed an interaction between national identification and temporal comparison (but not with social comparison) indicating that positive temporal comparison seemed to have a reduced effect (but still significant) for highly identified citizens. These results are supportive of the social identity approach to system justification and suggest that support for societal systems is a positive function of people’s personal and group interests.